Making the History of Computing Relevant IFIP WG 9.7 International Conference, HC 2013, London, UK, June 17-18, 2013, Revised Selected Papers - Tatnall, Arthur; Blyth, Tilly; Johnson, Roger; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed post-proceedings of the IFIP WG 9.7 International Conference on the History of Computing, HC 2013, held in London, UK, in June 2013. The 29 revised full papers presented were carefully reviewed and selected from numerous submissions. The papers cover a wide range of topics related to the history of computing and offer a number of different approaches to making this history relevant. These range from discussion of approaches to describing and analyzing the history through storytelling and education to description of various collections, working installations and reconstruction projects. The papers have been organized in the following topical sections: the importance of storytelling in museums; spotlight on some key collections and their future plans; thoughts on expanding the audience for computing history; spotlight on some research projects; integrating history with computer science education; putting the history of computing into different contexts; celebrating nostalgia for games - and its potential as Trojan horse; the importance and challenges of working installations; and reconstruction stories.
The importance of storytelling in museums -- Spotlight on some key collections and their future plans -- Thoughts on expanding the audience for computing history -- Spotlight on some research projects -- Integrating history with computer science education -- Putting the history of computing into different contexts -- Celebrating nostalgia for games - and its potential as Trojan horse -- The importance and challenges of working installations -- Reconstruction stories.
Keywords: Computer science; Education; Computer Science; History of Computing; Computers and Education; User Interfaces and Human Computer Interaction